Exploring Students’ Experiences of Story Telling Technique in English Speaking Learning in Junior High School - Rahmadhania, Sheila Nirmala; Chaerul, Andrie; Ahmad, Yousef Bani (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to seek how students’ experiences in using story telling technique as an English speaking learning. Story telling is one of the learning method to encourage student learning in developing skills and knowledge of speaking. Many researchers said that story telling is important in the field of education along with the times as a main characteristic in the quality of teaching and learning more active and creative, especially in English speaking learning. This qualitative descriptive focused on story telling as learning method on Junior High School students to find out their experiences in English speaking. The data were collected from observation, interview, and documentation. This study presents the results of students’ experiences in story telling technique as learning to speak English can provided new vocabulary, how to pronounced it correctly, and trained students’ English speaking skills. Thus, story telling technique is a learning method on students exercise has a positive impact on helping develop the quality of students speaking in a second language.